Impact of Safety Net Hospitals in the Care of the Hand-Injured Patient: A National Perspective. Issue 2 (August 2016) - Yuan, Frank; Chung, Kevin C.
Abstract : Summary: A clear disparity in the pattern and provision of surgical care exists, particularly for patients with vulnerable socioeconomic backgrounds. For hand-injured patients in particular, this discrepancy has been frequently shown in their receiving appropriate care. With the advent of the Affordable Care Act and with Medicaid expansion on the horizon, more patients will be requiring access to care. Safety net programs have been shown to provide equivalent levels of care for patients compared with non–safety net providers, and the survival of these hospitals for the disadvantaged is essential to providing quality care for this growing patient population. In this article, the authors review the factors that affect the barriers to care, the importance of safety net hospitals, the epidemiology of the hand-injured patient, and how the Affordable Care Act will impact these safety net programs.